The effect of recycled polycarbonate mixing ratio on the tensile strength of polycarbonate polymer - Nurul Fariha, Mohamad (2013)
Nowadays, plastic and metal are used as raw material at the industries for their product. Plastic can be divided into two types which are thermoset and thermoplastic. Thermoplastic usually used compare to thermoset because it can be recycled and molded to be manufactured as a new product. Polycarbonate is an example of thermoplastic that widely used in the industries. Polycarbonates are condensation polymers with many desirable properties. They exhibit very high thermal stability and have a high heat distortion temperature. The problem happened when there are many wastes of products made from polycarbonate. The objective of this study is to investigate the effect of recycled Polycarbonate mixing ratio on the tensile strength of Polycarbonate polymer. Therefore, the mold was designed to produce tensile bar as a specimen to achieve the objective. Polycarbonate was dried at temperature 80°C for 4 hours by using vacuum oven and then the materials was injected using the injection molding machine. Then, the product produced was used as recycled material and mixed with virgin polycarbonate with different percentages. There are five samples of recycled PC/virgin PC percentages: 0/100, 25/75, 50/50, 75/25 and 100/0 respectively. The mixed material was injected to produce the specimen. The specimens of each experiment was tested by using Universal Tensile Machine to determine the best percentage mixing of the recycled Polycarbonate with the virgin Polycarbonate that has highest tensile strength. From the result, the testing part showed the highest tensile stress at maximum load is 0% recycled of polycarbonate which is 54.22611 MPa. The second highest is Experiment 4 that has 75% recycled polycarbonate, which is 52.77886 MPa. In addition, the lowest tensile stress at maximum load is 25% recycled polycarbonate, which is 49.17192 MPa. Thus, the properties of specimen in experiment 1 have good properties such as high strength and excellent toughness compared to another. The higher tensile stress also shows that the material is more brittle and less ductile.